Pengukuran Kinerja Keuangan pada PT Bank Muamalat Indonesia (BMI) Periode 2019-2021 - Umiyati; Hosen, M. Nadratuzzaman; Qizam, Ibnu (Jurnal Ilmiah Wahana Akuntansi, 2023)
This study aims to determine the financial performance of Bank Muamalat Indonesia in the 2019-2021 period using the CAMEL method, RGEC and Altma Z Score analysis. The research sample is Bank Muamalat Indonesia using criteria that have been considered and desired by the researchers according to the research objectives. The results of the study show that during the 2019-2021 period, they experienced poor performance in terms of profitability, equity. However, different things occur in the capital ratio and capital adequacy which have more optimal performance than other ratios. Based on the results of the soundness level, steps to improve the condition of Bank Muamalat are by strengthening capital, followed by improving asset quality by completing the NPF